Geographical (natural and human) and economic factors for industries in the peripheral areas of Baghdad Governorate - Abed, Alaaa; Reda , Intisar (Al-Adab Journal, 2025)
The natural factors have a clear impact on the industries in the marginal areas of Baghdad Governorate, as their impact varies from one industry to another, including the climate factor. The climate is considered one of the important and influential factors in choosing the industrial location and its impact on the industry due to its elements, including temperature. High temperatures contribute to the revitalization of food industries, such as beverages and juices, during the summer, while the production of other industries, such as ice production, decreases in the winter. This has a clear impact on the choice of the type of industry in relation to the direction of the winds, as they have an impact on carrying pollutants coming from factories, including asphalt and construction industries such as brick production. The geological structure has a clear impact on the localization of industrial facilities, which is linked to the slope ratio of the land, its ruggedness, and the provision of services such as infrastructure services. As for the human factors and their impact on the industries in the study area, it has been revealed that the study area has a human base that can be trained and qualified to be utilized and prepared to work in industrial facilities. This is concurrent with the increase in the population in the city of Baghdad and the government’s direction in selecting the marginal areas of Baghdad Governorate to accommodate the population increase from the city center and to transfer and relocate industries to those areas, which will become an economic and industrial hub attracting future investments. Findings, Recommendations, and Conclusion. Baghdad Governorate is characterized by several factors that have played a role in the localization of industries in the study area. Among the most important of these natural factors is the geographical location in the middle of Iraq, and the suitable climate for various industries, which indirectly contributes to their attraction and impact on the industry. The role of the climate in the rise of temperatures in summer, reaching around (50°) degrees Celsius in August, has led to the attraction of certain industries, including food and beverage industries such as soft drinks, juices, ice production, and water bottling, which are localized in Madain District. Human resources are represented by the availability of an active population base that can be utilized to work in various industries, provided that they are trained and prepared to suit the nature of their assigned work. Regarding economic factors, land prices are considered encouraging factors for industrial localization, as well as the availability of raw materials and their market, which is important in attracting industries. Any disruption in these natural, human, and economic factors affects the, the growth and development of industries in the study area